Central centrifugal cicatricial alopecia: challenges and solutions - Herskovitz I; Miteva M (Dove Medical Press, 2016)
Ingrid Herskovitz, Mariya Miteva Department of Dermatology and Cutaneous Surgery, University of Miami L Miller School of Medicine, Miami, FL, USA Abstract: Central centrifugal cicatricial alopecia (CCCA) is the most common scarring alopecia among African American women. Data about epidemiology, etiology, genetic inheritance, and management are scarce and come from individual reports or small series. CCCA has been associated with hot combing and traumatic hair styling for years; however, studies fail to confirm it as the sole etiologic factor. It has been shown in a small series that CCCA can be inherited in an autosomal dominant fashion, with a partial penetrance and a strong modifying effect of hairstyling and sex. CCCA presents clinically as a central area of progressive irreversible hair loss that expands to the periphery. A patchy form has also been described. Dermoscopy is helpful to identify the optimal site for the biopsy, which establishes the diagnosis. Well-designed randomized controlled trials are needed to discover the optimal management. At this point, patients are advised to avoid traction and chemical treatments; topical and intralesional steroids, calcineurin inhibitors, and minoxidil can be helpful in halting the progression. Keywords: hair loss, alopecia, dermatoscopy, dermoscopy, trichoscopy, black scalp, African American, scarring alopecia